2003
DOI: 10.1038/sj.ijo.0802385
|View full text |Cite
|
Sign up to set email alerts
|

Screening for childhood obesity: international vs population-specific definitions. Which is more appropriate?

Abstract: AIM:The objectives of this study are: (1) to study the relation between body mass index (BMI), percentage-weight-for-height (PWH) and percentage body fat (PBF) in Singaporean Chinese children; (2) to assess the applicability of an international definition of obesity (the International Obesity Task Force (IOTF) BMI) as a screening tool to detect childhood obesity, as compared with the current Singapore population-specific definition using PWH. METHODS: A total of 623 Chinese children aged 6-11 y (321 males, 302… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 20 publications
8
45
0
Order By: Relevance
“…The highly specific but less sensitive nature of BMI-based classification systems has been documented repeatedly, despite variations in cutoffs used (Sardinha et al, 1999;Reilly et al, 2000;Fu et al, 2003;Neovius et al, 2004;Zimmermann et al, 2004). The estimates of sensitivity and specificity have, however, varied greatly in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly specific but less sensitive nature of BMI-based classification systems has been documented repeatedly, despite variations in cutoffs used (Sardinha et al, 1999;Reilly et al, 2000;Fu et al, 2003;Neovius et al, 2004;Zimmermann et al, 2004). The estimates of sensitivity and specificity have, however, varied greatly in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have defined paediatric obesity and overweight as the fattest 5 and 15%, respectively, in the sample (Lazarus et al, 1996;Reilly et al, 2000;Fu et al, 2003). This method sets the %BF-based prevalence to a fixed percentage, and even though individuals with higher %BF relative to the group may be identified, the cutoffs may vary between studies.…”
Section: Introductionmentioning
confidence: 99%
“…11 Diagnostic accuracy of national and 'international' obesity definitions Diagnostic accuracy of BMI for age depends on whether it is defined relative to national BMI reference data, or to the 'international' or 'IOTF' definitions of paediatric overweight and obesity. 12 Four published studies [13][14][15][16] have now made a direct comparison of the diagnostic ability of cutoffs based on national reference data (from the US, UK, and Singapore) with those recommended by the IOTF. All four found that the sensitivity of the IOTF obesity definition was much lower than that of definitions based on national reference data (such as BMI X95th percentile).…”
Section: Evidence Base On Diagnostic Accuracymentioning
confidence: 99%
“…Up to 40-50% of the fattest children were not identified as obese by the IOTF approach. [13][14][15][16] These studies also reported that the sensitivity of the IOTF definition was highly sex-specific. In the UK, for example, use of the IOTF approach has much lower sensitivity in boys than girls, 13 leading to the erroneous conclusion that obesity is more prevalent in girls than boys.…”
Section: Evidence Base On Diagnostic Accuracymentioning
confidence: 99%
See 1 more Smart Citation